Spying in America : Espionage from the Revolutionary War to the Dawn of the Cold War - Sulick, Michael J. (Book collections on Project MUSE., 2012)
Can you keep a secret? Maybe you can, but the United States government cannot. Since the birth of the country, nations large and small, from Russia and China to Ghana and Ecuador, have stolen the most precious secrets of the United States. Written by Michael Sulick, former director of CIA's clandestine service, Spying in America presents a history of more than thirty espionage cases inside the United States. These cases include Americans who spied against their country, spies from both the Union and Confederacy during the Civil War, and foreign agents who ran operations on American soil. Some of the stories are familiar, such as those of Benedict Arnold and Julius Rosenberg, while others, though less well known, are equally fascinating. From the American Revolution, through the Civil War and two World Wars, to the atomic age of the Manhattan Project, Sulick details the lives of those who have betrayed America's secrets. In each case he focuses on the motivations that drove these individuals to spy, their access and the secrets they betrayed, their tradecraft or techniques for concealing their espionage, their exposure and punishment, and the damage they ultimately inflicted on America's national security. Spying in America serves as the perfect introduction to the early history of espionage in America. Sulick's unique experience as a senior intelligence officer is evident as he skillfully guides the reader through these cases of intrigue, deftly illustrating the evolution of American awareness about espionage and the fitful development of American counterespionage leading up to the Cold War.